PEMAHAMAN MATERI PYTHAGORAS DENGAN PEMBELAJARAN INKUIRI BERBASIS KOMUNIKASI MATEMATIS DI SEKOLAH MENENGAH PERTAMA - Afriani, Dini; Suratman, Dede; Yusmin, Edy (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe quality of students' understanding in Pythagorean material is still low. This is because in teaching too concentrated on procedural matters, calculating counting, formula memorization, and giving low attention to the process of obtaining the concept of procedure or formula. The present research aims at (1) studying students’ activities in the mathematic-communication-based inquiry learning; (2) studing students’ understanding in Pythagoras material with the mathematic-communication-based inquiry learning. The research was conducted on 8th grade students at one roof Junior High School 4 in Pulau Maya. The research used descriptive analysis which had been modified as necessary. The data analysis procedure was conducted through Miles and Huberman qualitative analysis. The results in this study indicate that: (1) During the learning, drawing activity is the most widely indicated indicator by students compared with written text and mathematical expression activity; (2) students’ understanding in Pythagoras material improve having attended the mathematic communication-based inquiry learning.Keyword: Mathematic Communication-Based Inquiry Learning, Students’ Understanding.